The validity of physiological variables to assess training intensity in kayak athletes - Bishop, D. (International Journal of Sports Medicine, 2004)
It appears that training benefits are compromised if excessive training is performed at intensities that are either too low or too high. This suggests a need for accurate methods to monitor training intensity. It has been suggested that heart rate (HR) or lactate concentration ([La -]) can be used to accurately monitor training intensity. The purpose of the present study therefore, was to examine whether the relationship between HR, [La -] and intensity determined during a kayak graded exercise test (GXT) remained stable during constant-intensity kayak exercise. Sixteen trained kayak paddlers, (22 +/- 4 y, peak V.O (2) = 3.7 +/- 0.9 l x min (-1)) performed a GXT on a wind-braked kayak ergometer. They then performed a 20-min constant-load test on the kayak ergometer at a power output corresponding to their lactate inflection (LI) intensity. Eight subjects also performed a 20-min constant-load test at a power output corresponding to their lactate threshold (LT) intensity. Differences between constant-load and GXT values were determined using one-way ANOVA (p < 0.05). There were no significant differences between values for HR and V.O (2) derived from the GXT and those measured during both constant-load tests. However, while [La -] also provided a valid marker of the LI training intensity (1.8 +/- 0.3 v 2.1 +/- 0.8 mmol x l (-1)), [La -] did not provide a valid marker of the LT training intensity (3.8 +/- 0.7 v 5.1 +/- 1.4 mmol x l (-1)). These results suggest that HR, but not [La -1], is similar during both a GXT and constant-load exercise at the LT intensity.